25.6k views
7 votes
Solve the following system of equations by substitution
2x – 3y = -1
y = x - 1

User Voromax
by
4.9k points

1 Answer

1 vote

Answer:

(4, 3)

Explanation:

Plug in x - 1 where y is. The equation will turn in 2x - 3(x - 1) = -1. Distribute, and you'll have 2x -3x + 3 = -1. Combine like terms (2x and -3x) and you'll have -x + 3 = -1. Subtract 3 from both sides, and you'll have -x = -4. Divide by -x (or -1) on both sides, and you'll have x = 4. Since y = x - 1, y = 3, since 4 - 1 = 3. Sorry if this sounds repetitive btw. Good luck :D

User Shawnie
by
5.4k points